Gastric microbiome - M. Jauvain; E. Bessède (Microbiota in Health and Disease, 2023)
Considering the gastric microbiota, Helicobacter pylori is the most famous bacterium discovered in the 80s and is known to be implicated in gastric diseases. Its role in ulcer peptic disease and in gastric cancers is now very well described. However, other bacteria, like Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria and Fusobacteria, can reside in the stomach, and this review will present the different studies published in 2022 considering the gastric microbiome.